INTERACTION OF SUPERNOVA BLAST WAVES WITH WIND-DRIVEN SHELLS: FORMATION OF - Gvaramadze, V. V. (Одеські астрономічні публікації, 2017)
Most of middle-aged supernova remnants (SNRs) have a distorted and complicated appearance which cannot be explained in the framework of the Sedov-Taylor model. We consider three typical examples of such SNRs (Vela SNR, MSH15-52, G309.2-00.6) and show that their structure could be explained as a result of interaction of a supernova (SN) blast wave with the ambient medium preprocessed by the action of the SN progenitor’s wind and ionized emission.